Development of a Questionnaire for Prolonged Standing Jobs at Manufacturing Industry - Isa, Halim (2010)
Prolonged standing has been identified as a potential threat for occupational health of workers in manufacturing industry. To minimize occupational injuries associated with prolonged standing, a reliable tool is required to investigate the root of the problems so that alternative solutions could be proposed. The purpose of the study is to develop a questionnaire that specifically used to assess difficulties in prolonged standing jobs. Literature survey, series of mini workshops, and pilot study have been performed to develop the questionnaire. Based on the carried out case study, the questionnaire has shown a potential tool to manage prolonged standing jobs, however further work is required to establish the validity of the tool.